A study: comparing customers' perceptions towards Tabung Haji services and other banks: a case study of Tabung Haji in Wilayah Persekutuan and Melaka branch / Fazilah Asirop - Asirop, Fazilah (Faculty of Business and Management, 2004)
The objective to this study is to compare the depositor experiences and perception between Tabung Haji with others banks and to study the perception of depositor on staff of Tabung Haji. This study involved 1200 respondent of 12 Tabung Haji branches, which have 6 branches for each branch. For each branches 100 respondent were selected to answer the questionnaire. A set of questionnaire we give to the respondent while they are waiting for transaction in the counter service.